Synthesis of oximes of pyranoneoflavons and spiropyranoneoflavons - Moskvina, V.S.; Krasylov, I.V.; Khilya, V.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
Preparative procedures for the preparation of pyranoneoflavones and spiropyranoneoflavones of the linear structure, which are synthetic analogs of the natural graveolone, are developed, and their interaction with hydroxylamine hydrochloride is investigated. It is shown that the interaction proceeds selectively with the formation of the corresponding oximes, convenient reagents with additional functional groups for a subsequent modification.